The dog that barks: Understanding propaganda campaigns on territorial disputes - WANG, Frances Yaping (Institutional Knowledge at Singapore Management University, 2020)
Why do authoritarian states promote media coverage of foreign disputes in some contexts, but censor coverage in others? The use of media on matters of foreign policy is prevalent in both autocracies and democracies, yet their functions, especially in autocracies, are not well understood. This dissertation seeks to explain a statecraft autocratic leaders are especially adept at and are commonly engaged in – propaganda campaigns on territorial disputes. This project thus provides a window into the domestic constraints and motivations of authoritarian foreign policy and the resulting statecraft in managing its domestic publics on foreign policy issues. In explaining the adoption or non-adoption of propaganda campaigns, I develop a (mis)alignment theory that proposes two independent variables – existing public opinion and state foreign policy intent. I argue that together and interactively, the juxtaposition of these conditions drives a popular autocrat to employ media as a tool of statecraft to “bridge” the opinion gap between the public and the state. When the gap is between a pacifist public and a hardline state, the state uses a propaganda campaign to mobilize public support for a potentially risky policy. Conversely, when the gap is between a militant public and a government favoring peaceful resolutions, the state might counterintuitively also adopt a propaganda campaign, but in this case to subdue public opinion. Like a dog that barks but does not bite, autocratic leaders could use propaganda campaigns to keep up the appearances of a hard stand, thus to fend off nationalist criticisms, to save face, and to maintain social stability, while allowing the public to let off steam through the echoing and the venting functions of the media. An absence of the gap would explain an absence of propaganda campaigns. The pacifying propaganda campaign is worth special notion because it is not commonly understood, but is commonly practiced by authoritarian states, and increasingly so as a way in dealing with rising nationalist sentiment in many of these countries. A medium-n congruence test of nineteen Chinese diplomatic crises on territorial disputes and process-tracing four of these crises, using primary sources and content analysis of the Chinese official newspaper People’s Daily, render strong support for this theory. This project contributes to domestic theories of international disputes by focusing on the role of public opinion and media in an authoritarian context. It also contributes to the Comparative Politics literature on authoritarian public opinion by moving the testing field of the complex state-society relations in authoritarian states from domestic politics to the international policy arena.